The Mosoghi sustainability model for the water management of companies - Laureano Valentín, Gaudencio (2022)
The Companies do not have a way to measure the sustainability of the water management that they apply in their activities. Therefore, they do not have a horizon for the continuous improvement of said management. The MOSOGHI Model proposes an alternative solution to this problem. This Model organized with ethical principles proposed by UNESCO in Istanbul in 2009 and sustainability indicators for Water Management, facilitates such measurement. Through a documentary analysis, the application of the principles of ethics and the RUFOI system, sustainability indicators for Water Management are obtained. By using mathematical and statistical formulas, the degree of sustainability is obtained based on indicators and indices. By weighing the sustainability indicators and indices, we determine the Sustainability Degree with which Water Management is evaluated. As they are mathematical and statistical data, we could carry out simulations to visualize the results of the Degree of sustainability of the Water Management of a Company, but as we have real data of the application of the MOSOGHI Model in the Water Management of the Milpo Company, on this occasion we show the results of the measurement of the sustainability of said Management.